Increase in root nodulation and crop yield of soybean by native Bradyrhizobium japonicum strains - Dhami, Namraj; Prasad, Braj Nandan (Botanica Orientalis: Journal of Plant Science, 2010)
Native strains of Bradyrhizobium japonicum were tested for their effectiveness on nodulation, crop yield and nitrogen fixation in soybean (Glycine max). B. japonicum strains were isolated from soybean root nodules collected from different agro-climatic regions of Far Western Nepal, viz. Dipayal (607 m asl), Dadeldhura (1097 m asl), Silgadhi (1209 m asl) and Bajura (1524 m asl). The strains were characterized by studying colony characteristics, growth response with Congo red and Bromothymol blue, and Gram staining. The native bradyrhizobial strains were authenticated by performing infection test on soybean seedlings. All the four strains were found compatible and effective on root nodulation, crop yield and soil nitrogen (N) content. Inoculation of these strains increased soybean root nodulation by 247-343% and crop yield by 45-204%. There was strong positive correlation (r = 0.982) between number of root nodules and crop yield, which suggest that optimization of root nodulation by inoculating compatible and effective B. japonicum strains significantly increase the soybean crop yield. Soil N content of inoculated experimental pots was increased by 13-33%. However, variability among different strains was observed in their effect on root nodulation and yield performance. B. japonicum strain collected from Silgadhi was found to be the most effective in increasing nodule number and crop yield by 343% and 204% respectively. Key-words: Glycine max; gram staining; inoculation; nitrogen fixation DOI: 10.3126/botor.v6i0.2902 Botanica Orientalis - Journal of Plant Science (2009) 6: 1-3